Common Styles of thinking among class room teacher students and its relationship with some variable "A field study of students of classroom teacher" (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study aimed at investigating the styles of thinking of class room teacher students in the College of Education at Tishreen University, and to know the impact of the variables of ( gender, school year and the type of secondary school certificate) on styles of thinking of those students, and to achieve the aims of the study a Questionnaire was designed included some items , then the researcher assured its validity and reliability and its suitability to the purposes of this study , the researcher distributed it on a stratified random sample consisted of ( 287 ) students. The descriptive approach has been used.The current study reached at some results , some of them are as follows :-  The hierarchical style of thinking is prevalent to the members of sample.-The members of the study sample are global ,liberal and external in their thinking.- The study didn’t  show significant differences in  thinking styles according to the variable of gender except for the styles of oligarchic and the anarchic in favor of student males .-The  study also didn’t  show significant  differences in  thinking styles according to the two  variables  of school year and the type of secondary school certificate , except for the monarchic style which was in favor of the fourth year students and the scientific secondary school certificate students .The study suggested including the styles of thinking in the curricula in the College of Education, and diversifying instructional methods and evaluation styles in line with students’ styles of thinking.